Managing Uncertainty: How Trend-forecasting Agencies Conquer the Global Fashion Industry - Kusimova, Tamara (Journal of Economic Sociology, 2017)
This article presents a review of Jenny Lantz’s book The Trendmakers: Behind the Scenes of the Global Fashion Industry. The book engages in a sociological and economic inquiry into trend forecasting in the fashion industry. Trend forecasting is a special kind of business that focuses on predicting future trends in consumers’ taste. Making such decisions usually seems intuitive: In distinguishing between “fashionable” and “unpopular” products, people commonly rely on subjective opinions. Furthermore, the fashion business is an example of extremely turbulent aesthetic goods market in which any forecasting seems difficult. Using the results obtained from nearly one hundred in-depth interviews, Lantz unveils the magic of the trend-hunting business. Referring to classical sociological theories of fashion, including Pierre Bourdieu’s theory of power and symbolic capital, Lantz describes how trend forecasting agencies — including global organizations like WGSN and Trend Union, as well as local companies like Promostyl — achieve legitimacy by working with consultants, buyers, fashion designers, and social influencers. The book reveals that trend forecasting is not about future-telling; rather, it is more about “future-feeling” based on shared perceptions of class, status, and taste. Lantz also provides an insight into developing markets of BRICS countries, including China, Brazil, India, and Russia. Although the section on Russia is quite brief, it contains useful information about big retailers and Russian designers, and it may be useful for further research on the Russian market. The book may attract sociologists, economists, and business students, as well as a wider audience interested in the global fashion industry.